If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -9 = 3(a + -3) Reorder the terms: -9 + 4a = 3(a + -3) Reorder the terms: -9 + 4a = 3(-3 + a) -9 + 4a = (-3 * 3 + a * 3) -9 + 4a = (-9 + 3a) Add '9' to each side of the equation. -9 + 9 + 4a = -9 + 9 + 3a Combine like terms: -9 + 9 = 0 0 + 4a = -9 + 9 + 3a 4a = -9 + 9 + 3a Combine like terms: -9 + 9 = 0 4a = 0 + 3a 4a = 3a Solving 4a = 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 4a + -3a = 3a + -3a Combine like terms: 4a + -3a = 1a 1a = 3a + -3a Combine like terms: 3a + -3a = 0 1a = 0 Divide each side by '1'. a = 0 Simplifying a = 0
| 2x+23=4(x+5) | | 4a-9=3(a-9) | | x+2.3=4.1 | | (6x-5)/4=3 | | 3r+6=48+11r | | 5c-6=-9 | | 12-8-3= | | 12x+4=3(4-2) | | 3(7x-6)=5(2+5x) | | 96=-16t^2+120t+96 | | 3(2x-5)+x=6 | | 8x-9=2x+27 | | -5(a-1)+2(3a+4)=10a-3(2a+5) | | -18y^2-9y+5=0 | | T*8=46 | | 1.5xX-2.5=3.5xX+13.7 | | Z*9=54 | | 9(v-4)=3v+18 | | 6(v-2)-8v=-4 | | 4(6z-1)-3(z+4)=16(z+1) | | N=0.04x-79.06 | | (x+1)(x^3+7x^2+5x+4)= | | 10t=-22 | | x-27=-26 | | -3(4y-5)+2(2y+6)= | | 20a^2b^2-5a^4b^4= | | -3(t-9)-(t+7)=9 | | -4(x+6)= | | 6+5y=17 | | 22x-11=(x+5)(x+5) | | 3[2x-3(7x+y)]= | | 4a+5b=-6 |